Plant diversity does not buffer drought effects on early‐stage litter mass loss rates and microbial properties. (29th May 2013) - Vogel, Anja; Eisenhauer, Nico; Weigelt, Alexandra; Scherer‐Lorenzen, Michael
Abstract: Human activities are decreasing biodiversity and changing the climate worldwide. Both global change drivers have been shown to affect ecosystem functioning, but they may also act in concert in a non‐additive way. We studied early‐stage litter mass loss rates and soil microbial properties (basal respiration and microbial biomass) during the summer season in response to plant species richness and summer drought in a large grassland biodiversity experiment, the Jena Experiment, Germany. In line with our expectations, decreasing plant diversity and summer drought decreased litter mass loss rates and soil microbial properties. In contrast to our hypotheses, however, this was only true for mass loss of standard litter (wheat straw) used in all plots, and not for plant community‐specific litter mass loss. We found no interactive effects between global change drivers, that is, drought reduced litter mass loss rates and soil microbial properties irrespective of plant diversity. High mass loss rates of plant community‐specific litter and low responsiveness to drought relative to the standard litter indicate that soil microbial communities were adapted to decomposing community‐specific plant litter material including lower susceptibility to dry conditions during summer months. Moreover, higher microbial enzymatic diversity at high plant diversity may have caused elevated mass loss of standard litter. Our results indicate that plant diversity loss and summer drought independently impede soil processes. However, soil decomposer communities may be highly adapted to decomposing plant community‐specific litter material, even in situations of environmental stress. Results of standard litter mass loss moreover suggest that decomposer communities under diverse plant communities are able to cope with a greater variety of plant inputs possibly making them less responsive to biotic changes.